Acute iatrogenic complications after mitral valve repair. Issue 12 (23rd October 2022) - Paparella, Domenico; Squiccimarro, Enrico; Di Mauro, Michele; Katsavrias, Kostas; Calafiore, Antonio M.
Abstract: Background and Aim of the Study: Mitral valve repair is the procedure of choice to correct mitral regurgitation. However, some dangerous iatrogenic complications can occur at the end of the procedure. Therefore, we sought to review the most frequent and clinically relevant acute iatrogenic complication following mitral valve repair. Methods: A thorough review of the literature has been performed. Criteria for considering studies for this non‐systematic review were as follows: observational and interventional studies investigating the acute iatrogenic complications following mitral valve repair, and essential review studies pertinent to the topic. Results: The most frequent is the systolic anterior motion. Due to a systolic dislocation of the anterior leaflet toward the outflow tract, it causes both obstruction of the outflow tract and mitral regurgitation. Often it is due to excess of catecholamines or to reduced filling of the left ventricle but sometimes needs further surgical maneuvers, focused on moving posteriorly the coaptation line. It can be obtained by shortening the posterior leaflet or increasing the size of the ring or applying an Alfieri stitch to limit the movements of the anterior leaflet. Another complication, often underdiagnosed and potentially lethal, is the injury of the circumflex artery that happens at the level of the anterolateral commissure or P1 zone. Two mechanisms are involved. The first one is the direct injury of the artery by a stitch (roughly 25% of the patients present a distance artery‐annulus <3 mm. The second one is the distortion of the artery, attracted toward the annulus by a misplaced stitch. The attraction causes kinking with stenosis of different degrees till functional occlusion. However, the artery has to be far from the annulus and the atrial tissue has to be stiff and resistant, as after an infective process, to move the circumflex artery toward the annulus without tearing. Positioning the stitches very close to the mitral leaflets in the dangerous area is the only prevention to the complication. The treatment in the operating theater is partial or total removal/reimplantation of the annular sutures or coronary artery bypass grafting to the circumflex area. If the injury is demonstrated only after coronary angiography, percutaneous revascularization can be attempted before further surgical treatment. Conclusions: Acute iatrogenic complication after mitral repair exists and may compromize patient outcome. Raising awareness about these issues, the precautions to prevent them, and the manners of resolution is therefore mandatory.